Test-retest reliability of muscle strength and physical function tests in 6-9-year-old children - Thams, L.; Hvid, L. G.; Damsgaard, C. T.; Hansen, M. (Measurement in Physical Education and Exercise Science, 2021)
We aimed to assess the test-retest reliability of five muscle strength and physical function tests in healthy children. Forty-one children (6-9years) were tested three times 4-10days apart. The test protocol included maximal isometric leg press, hand grip strength, squat jump, long jump, and a 30-sec sit-to-stand test (STST). When comparing test round 1 with 2 and 2 with 3, we found good-to-excellent retest reliability of leg press (intraclass correlation coefficient, ICC=0.87 and ICC=0.94), hand grip (ICC=0.90 and ICC=0.94), and long jump (ICC=0.86 and ICC=0.87). Initially, there was a moderate reliability of squat jump (ICC=0.71), which was improved to ICC=0.82 (round 2-3). Similarly, reliability of STST was improved from low (ICC=0.63) to moderate reliability (ICC=0.78). We conclude that leg press, hand grip, squat jump, and long jump tests are reliable measurements of children`s muscle strength and function, even without familiarization. Contrary, STST requires familiarization to ensure adequate reliability.